Evaluation of nicosulfuron for control of speargrass (Imperata cylindrica) in Nigeria - Lum, A.F.; Chikoye, David; Adesiyan, S.O. (Informa UK Limited, 2004)
Nicosulfuron is a new alternative herbicide for post-emergence control of perennial weeds in maize. Field studies were conducted to evaluate the response of four maize cultivars (Low-N-Pool, TZB-SR, Oba Super-1 and Oba Super-2) and speargrass to different rates of nicosulfuron (35, 70, and 105 g a.i. ha − 1). Hand-weeded and unweeded plots were controls. All plots that received nicosulfuron had significantly lower speargrass shoot biomass than the unweeded control 3 weeks after treatment and at crop harvest. Maize biomass was highest in the weeded control in both years. In 2000, maize biomass in plots that received 35 g a.i. ha − 1 of nicosulfuron was similar to that in the unweeded control, and in both cases was higher than in all the other nicosulfuron treatments. In 2001, all rates of nicosulfuron produced significantly higher maize biomass than the unweeded control. Higher maize grain yield was obtained from 70 and 105 g a.i. ha − 1 than from 35 g a.i. ha − 1. All the cultivars responded similarly to nicosulfuron. A linear regression equation is given for grain yield and speargrass biomass. Our results suggest that nicosulfuron has the potential for effective speargrass control in Nigeria.